Numerical method for solving fuzzy polynomials and fuzzy differential equations - Noor'ani Hj. Ahmad (Terengganu: Universiti Malaysia Terengganu, 2013)
Uncertainty and vagueness occur in many real life problems. Uncertainty may exist in the experimental process, data collection and process measurement. The uncertainty information can be modelled and formulated into fuzzy funtions. Therefore fuzzy set theory is incorporated to overcome this problem